Biogeochemical impacts of sewage effluents in predominantly rural river catchments: Are point source inputs distinct to background diffuse pollution?. (1st June 2022) - Richards, Samia; Bidgood, Lucy; Watson, Helen; Stutter, Marc
Abstract: Discharge of treated sewage effluent to rivers can degrade aquatic ecosystem quality, interacting with multiple stressors in the wider catchment. In predominantly rural catchments, the river reach influence of point source effluents is unknown relative to complex background pressures. We examined water column, sediment and biofilm biogeochemical water quality parameters along river transects (200 m upstream to 1 km downstream) during summer at five wastewater treatment works (WWTW) in Scotland. Treated sewage effluent (subset, n = 3) pollutant concentrations varied between sites. Downstream concentration profiles of water and sediment biogeochemical parameters showed complex spatial changes. A hypothesised point source signature of elevated concentrations of pollution immediately downstream of WWTW then a decaying pollution 'plume' did not commonly occur. Instead, elevated soluble reactive phosphorus (SRP), ammonium and coliforms (maximum 0.23 mgP/l, 0.33 mgN/l and >2 × 10 6 MPN/100 ml) occurred immediately downstream of two WWTW, whereas some downstream pollutant concentrations decreased. Microbial substrate respiration responses only differed 1 km downstream. Significantly greater concentrations of sediment metal occurred >500 m downstream, likely due to the redeposition of historic contaminated sediments. Significantly lowered chlorophyll- a downstream of one WWTW coincided with elevated metals, despite water SRP and sediment P increases. Overall, stress caused to microbes and algae by effluent contaminants outweighed the subsidy effect of WWTW nutrients. We observed variable effluent flows to the rivers limited localised pollution downstream of WWTW and overall influence of arable land cover on river water quality. Together, this challenges views of consistently discharging point sources impacting low dilution sensitive rivers in summer contrasting with 'diffuse' sources. Thus, river water column and benthic compartments are altered at varying scales by point source effluents in combination with rural catchment pollution sources, both discrete (e.g. farmyards and septic tanks) and diffuse. Graphical abstract: Image 1 Highlights: Process studies of rural wastewater effluent aquatic impacts are limited. River water, sediment and biofilm longitudinal transects were studied in summer. Pollutant plume and decay behaviour seldom occurred after effluent inputs. Metal, nutrient and ecosystem response change profiles were diverse. Point and diffuse source river impacts seem synergistic but often inseparable.